A sensory signal related to left-right symmetry modulates intra- and interlimb cutaneous reflexes during locomotion in intact cats - Mari, Stephen; Lecomte, Charly G.; Merlet, Angèle N.; Audet, Johannie; Harnie, Jonathan; Rybak, Ilya A.; Prilutsky, Boris I.; Frigon, Alain (Frontiers in Systems Neuroscience, 2023)
During locomotion, cutaneous reflexes play an essential role in rapidly responding to an external perturbation, for example to prevent a fall when the foot contacts an obstacle. In cats and humans, cutaneous reflexes involve all four limbs and are task- and phase modulated to generate functionally appropriate whole-body responses. To assess task-dependent modulation of cutaneous interlimb reflexes, we electrically stimulated the superficial radial or superficial peroneal nerves in adult cats and recorded muscle activity in the four limbs during tied-belt (equal left-right speeds) and split-belt (different left-right speeds) locomotion. We show that the pattern of intra- and interlimb cutaneous reflexes in fore- and hindlimbs muscles and their phase-dependent modulation were conserved during tied-belt and split-belt locomotion. Short-latency cutaneous reflex responses to muscles of the stimulated limb were more likely to be evoked and phase-modulated when compared to muscles in the other limbs. In some muscles, the degree of reflex modulation was significantly reduced during split-belt locomotion compared to tied-belt conditions. Split-belt locomotion increased the step-by-step variability of left-right symmetry, particularly spatially. These results suggest that sensory signals related to left-right symmetry reduce cutaneous reflex modulation, potentially to avoid destabilizing an unstable pattern.